The contribution of X-ray polar blowout jets to the solar wind mass and energy. Issue Volume 8:Issue S300(2013) (6th January 2014) - Poletto, Giannina; Sterling, Alphonse C.; Pucci, Stefano; Romoli, Marco
Abstract: Blowout jets constitute about 50% of the total number of X-ray jets observed in polar coronal holes. In these events, the base magnetic loop is supposed to blow open in what is a scaled-down representation of two-ribbon flares that accompany major coronal mass ejections (CMEs): indeed, miniature CMEs resulting from blowout jets have been observed. This raises the question of the possible contribution of this class of events to the solar wind mass and energy flux. Here we make a first crude evaluation of the mass contributed to the wind and of the energy budget of the jets and related miniature CMEs, under the assumption that small-scale events behave as their large-scale analogs. This hypothesis allows us to adopt the same relationship between jets and miniature-CME parameters that have been shown to hold in the larger-scale events, thus inferring the values of the mass and kinetic energy of the miniature CMEs, currently not available from observations. We conclude our work estimating the mass flux and the energy budget of a blowout jet, and giving a crude evaluation of the role possibly played by these events in supplying the mass and energy that feeds the solar wind.